Place Branding Destinasi Wisata Pantai Bidadari Desa Sugih Waras Melalui Media Komunikasi Visual - Muhammad Renaldi Renald; Desy Misnawati; Afta Apriansyah (Yayasan Literasi Sains Indonesia, 2022)
Banding Agung district is one of ogan komering ulu selatan regency which puts a lot of tourism potential. One of them is bidadari beach which is in the village of sane sugih, bidadari beach has its own uniqueness and beauty because it faces directly mount seminung, and surrounded by rice fields and lake ranau and bukit barisan. The purpose of this research is to create a brand by creating an identity and implementing design strategies so as to increase the attractiveness of local or foreign tourists to the angel beach. The research approach used is a descriptive qualitative approach. The object of this research is bidadari beach sugih waras village while the subject of this investigation is the head of tourism and culture office, head of environment office, camat district banding agung, head of sugih waras village, bidadari coast guard and sane sugih village community. Data collection techniques use observation, interview, and documentation techniques. The results of this study are expected with the place branding of the beach of the sane sugih village attracting local and foreign tourists to visit.